Physiological and biochemical impacts of silicon against water deficit in sugarcane - Bezerra, Breno Kennedy Lima [UNESP]; Lima, Giuseppina Pace Pereira [UNESP]; dos Reis, André Rodrigues [UNESP]; Silva, Marcelo de Almeida [UNESP]; de Camargo, Mônica Sartori (Springer Nature, 2019)
Silicon (Si) has been reported to minimize the impacts of water deficit, even though it is not considered an essential plant element. Sugarcane is highly impacted by water deficit and has a particular and complex mechanism to address this stressful condition. Although sugarcane is an Si-accumulating plant, there are few results on the association between Si and water deficit, and physiological and biochemical responses are unclear for this crop. This study investigated the physiological and antioxidant defense system responses in drought-tolerant (RB86-7515) and drought-sensitive (RB85-5536) sugarcane cultivars grown in soil with and without silicon fertilization and subjected to water deficit for 30 and 60 days during the tillering (first experiment) or grand growth (second experiment) phases. Four replications were evaluated in both experiments. Silicon was used at a rate equivalent to 600 kg ha−1 Si as calcium magnesium silicate (108.4 g kg−1 Si; 274 g kg−1 Ca; 481 g kg−1 Mg), which was applied in soil 11 weeks before sugarcane was transplanted. Silicon fertilization improved physiological responses by increasing the water potential and relative water content in the leaves during the tillering and grand growth phases. Additionally, Si increased proline concentrations and/or superoxide dismutase (SOD) and/or ascorbate peroxidase (APX) levels in drought-tolerant and drought-sensitive cultivars under water deficit. These results suggested that Si could play a role in the detoxification of excessive ROS production by increasing proline levels or APX activities in sugarcane grown under water deficit.
Keywords: Antioxidant enzymes; Beneficial element; Drought; Plant nutrition; Saccharum spp